Attracting and retaining health workers in rural areas: investigating nurses' views on rural posts and policy interventions - Goodman Catherine; English Michael; Masamo Eunice; Wafula Jackline; Mudhune Sandra; Mullei Kethi; Lagarde Mylene; Blaauw Duane (BMC, 2010)
Abstract Background Kenya has bold plans for scaling up priority interventions nationwide, but faces major human resource challenges, with a lack of skilled workers especially in the most disadvantaged rural areas. Methods We investigated reasons for poor recruitment and retention in rural areas and potential policy interventions through quantitative and qualitative data collection with nursing trainees. We interviewed 345 trainees from four purposively selected Medical Training Colleges (MTCs) (166 pre-service and 179 upgrading trainees with prior work experience). Each interviewee completed a self-administered questionnaire including likert scale responses to statements about rural areas and interventions, and focus group discussions (FGDs) were conducted at each MTC. Results Likert scale responses indicated mixed perceptions of both living and working in rural areas, with a range of positive, negative and indifferent views expressed on average across different statements. The analysis showed that attitudes to working in rural areas were significantly positively affected by being older, but negatively affected by being an upgrading student. Attitudes to living in rural areas were significantly positively affected by being a student at the MTC furthest from Nairobi. During FGDs trainees raised both positive and negative aspects of rural life. Positive aspects included lower costs of living and more autonomy at work. Negative issues included poor infrastructure, inadequate education facilities and opportunities, higher workloads, and inadequate supplies and supervision. Particular concern was expressed about working in communities dominated by other tribes, reflecting Kenya's recent election-related violence. Quantitative and qualitative data indicated that students believed several strategies could improve rural recruitment and retention, with particular emphasis on substantial rural allowances and the ability to choose their rural location. Other interventions highlighted included provision of decent housing, and more rapid career advancement. However, recently introduced short term contracts in named locations were not favoured due to their lack of pension plans and job security. Conclusions This study identified a range of potential interventions to increase rural recruitment and retention, with those most favored by nursing students being additional rural allowances, and allowing choice of rural location. Greater investment is needed in information systems to evaluate the impact of such policies.